Spirometric alterations caused by hemodialysis. Their relation to changes in the parameters commonly used to measure hemodialysis efficiency. - Alves, J (1989)
The Forced Expiratory Volume in the 1st second (FEV1) and the Forced Vital Capacity (FVC) was determined before and after a hemodialysis (HD), in 61 patients suffering from chronic renal failure (CRF). Before and after the same HD the value of the following parameters were determined: Na; K; Cl; Urea; Creatinine, Ca; P and hematocrit. We found the following values: initial FEV1 91.68%, final FEV1 100.35%, (P less than 0.001); initial FVC 87.4%, final FVC 95.87% (P less than 0.001). The 61 patients were separated in two sub-groups. In the first the FEV1 variation less than or equal to 8%, while in the second it was greater than 8%. The mean variation of the other parameters was determined in both sub-group. No significant difference was found between them. On the other hand a significant correlation was found (r = 0.06, P less than 0.03) between the improvement of pulmonary function and the ponderal loss. The correction of the hydrosaline overload seems to be an important factor in the reported spirometric improvement.